EVALUASI PROGRAM PEMBANGUNAN INFRASTRUKTUR DENGAN DANA DESA DI KABUPATEN KARANGASEM - Wirapraja Mahatama, I Kadek Badradnyana; Jaya, Nyoman Martha; Adnyana Putera, I Gusti Agung (JURNAL SPEKTRAN; Vol 9 No 2 (2021), 2021)
The current government focuses on the development of the village itself by creating a dana desa program. The research objectives are to evaluate the process of village development with the dana desa program in Karangasem Regency, to analyze the value of legal aspects, aspects of human resources, social aspects, and aspects of the use of technology & information in influencing the success of the dana desa program, and to analyze the solutions to the identified obstacles. This study uses a qualitative descriptive method by looking at the results of open questionnaires, closed questionnaires, interviews and reviewing village fund documents. In the closed questionnaire analysis using SEM-PLS analysis using the SmartPLS program. The evaluation results from the legal aspect, human resource aspect, social aspect, financial aspect, and information technology aspect in the process of implementing the dana desa program are in good category. In the process of implementing the village fund program, various obstacles were identified. All aspects reviewed have a significant effect on the success of the implementation of the Dana Desa program. Legal aspects have the most significant positive influence on the success of the Dana Desa program, followed by information technology aspects, social aspects, financial aspects, and HR aspects respectively.. One of the solutions to the identified problems is to increase the competence of human resources in the village to be able to carry out the dana desa program properly.